The Impact of Learning Dacilities and Learning Discipline for the Result Grade VII SMP Negeri 7 Pematang Siantar - Ivan Rivaldo Purba; Anton Luvi Siahaan; Sotarduga Sihombing (International Journal of Integrated Science and Technology, 2023)
This research aims to find out how learning facilities and discipline influence the learning outcomes of class VII students at SMP Negeri 7 Pematang Siantar. The variables in this research are learning facilities and discipline as independent variables and learning outcomes as dependent variables. This type of research is quantitative descriptive research, with a population of all class VII students at SMP Negeri 7 Pematang Siantar totaling 222 . students and the research sample was 145 students selected using random sampling techniques . Data collection techniques use observation and questionnaires, while data analysis techniques use validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity, multiple linear regression, t tests, f tests, and coefficient of determination tests (R2). ​The results of this research indicate that there is no positive and significant influence between learning facilities on the learning outcomes of class VII students at SMP Negeri 7 Pematang Siantar as seen from the tcountl<ttable or 1.032<1.6556. There is a positive and significant influence between learning discipline on the learning outcomes of class VII students at SMP Negeri 7 Pematang Siantar as seen from the value of tcount>ttable or 3.338> 1.6556 . There is a positive and significant influence between learning facilities and discipline on the learning outcomes of class VII students at SMP Negeri 7 Pematang Siantar as seen from the fcount>ftable value or 6.416>3.06 and the significant value is 0.001<0.05.